Reduced death rates of elite Australian Rules footballers compared to age-matched general population. Issue 9 (September 2022) - Orchard, John W.; Orchard, Jessica J.; Semsarian, Chris; La Gerche, Andre; Driscoll, Timothy
Abstract: Objectives: To determine age-matched death rates of current and retired elite male Australian football players (Australian and/or Victorian Football League) with the general population. Design: Analysis of publicly-available birth, debut and death data for all Australian Victorian Football/Victorian Football League players who debuted prior to (and were still alive at) the start of 1971 or debuted 1971–2020. Methods: Wikipedia was used to source the dates of death (or record that the player was alive in 2021) for the cohort. New players became part of the cohort for analysis on debut and existing cohort members left it at death. Actual death rates (per year and per decade) were then compared to expected deaths, based on age-specific population death rates. Results: There were 5400 players and ex-players in the cohort at the start of 1971 (average age 47.3) and a further 4532 players debuted between 1971 and 2020 inclusive (a total of 9932 players). The expected deaths for the cohort in this 50-year period were 4955, but only 3914 deaths occurred (Standardized Mortality Ratio 0.79, 95 %CI 0.76–0.82). For younger members of the cohort (age <50) the discrepancy between expected (222) and actual (98) deaths was also significant (Standardized Mortality Ratio 0.44, 95 %CI 0.35–0.56). Conclusions: We conclude that the death rates of elite male Australian footballers are lower than the reference general population, similar to other studies of elite athletes. Some of this may be explained by "healthy cohort" selection bias, a limitation which affects almost all studies in this genre.